Immune response and cytokine status at varicose vein disease of pelvis minor in women - A. I. Gus (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
The article describes participation of immune system in pathogenesis of varicose vein of pelvis minor. The study revealed elevation of proinflammatory cytokines, discovered disturbances in cellular and humoral units of immunity. Indicated changes are evidence for inflammatory character of changes in venous vascular wall, causing its destruction and varicose dilatation.